2015
DOI: 10.1126/science.1260922
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of active neural circuits in vivo with designed calcium integrators

Abstract: The identification of active neurons and circuits in vivo is a fundamental challenge in understanding the neural basis of behavior. Genetically encoded calcium (Ca(2+)) indicators (GECIs) enable quantitative monitoring of cellular-resolution activity during behavior. However, such indicators require online monitoring within a limited field of view. Alternatively, post hoc staining of immediate early genes (IEGs) indicates highly active cells within the entire brain, albeit with poor temporal resolution. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
431
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 412 publications
(449 citation statements)
references
References 61 publications
17
431
0
1
Order By: Relevance
“…However, studies in zebrafish can go beyond a wiring diagram to a dissection of the in vivo functions of connections. Using multiphoton calcium imaging in fish carrying calcium sensors, it is possible to record neuronal activity simultaneously throughout the brain (Friedrich et al 2013;Renninger and Orger 2013;Fosque et al 2015). Neural networks involved in visual activity, hunting behavior, and navigation have already been defined (Ahrens et al 2013;Muto et al 2013;Bianco and Engert 2015;Romano et al 2015).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, studies in zebrafish can go beyond a wiring diagram to a dissection of the in vivo functions of connections. Using multiphoton calcium imaging in fish carrying calcium sensors, it is possible to record neuronal activity simultaneously throughout the brain (Friedrich et al 2013;Renninger and Orger 2013;Fosque et al 2015). Neural networks involved in visual activity, hunting behavior, and navigation have already been defined (Ahrens et al 2013;Muto et al 2013;Bianco and Engert 2015;Romano et al 2015).…”
Section: Future Directionsmentioning
confidence: 99%
“…This new class of small-molecule Ca 2+ indicator yields ap ermanent fluorescent signal that could enable simpler assays for high-throughput screening or the post hoc mapping of active cells in genetically intractable organisms.A dditionally,our modular synthetic strategy should facilitate improvements to this probe,such as modulating the Ca 2+ affinity, [2d, 15] altering the properties of the released fluorophore, [16] increasing the two-photon cross-section of the photocage by using the indoline scaffold, [9a,17] and changing selectivity to other ions that are similarly unable to elicit chemical reactions on their own (e.g.,N a + ). [2c, 18] Finally,u nlike the genetically encoded systems, [5,6] the flexibility of this small-molecule scaffold opens the door for pharmacological agents or chemical gene inducers to be photocaged and released using a" functional photochemistry" approach, allowing sophisticated biological experiments where active cells are selectively targeted for chemical manipulation.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In particular, caging af luorophore with such an ion-sensitive photocage would yield af luorescent ion "snapshot indicator" or "integrator" that would permanently record increased ion concentration during an illumination-defined time period. Integrator systems based on fluorescent proteins [5] and rhodopsins [6] have been described recently,b ut small-molecule ion integrators remain unknown. This currently limits the use of such probes to biological systems that are amenable to genetic manipulation.…”
mentioning
confidence: 99%
“…CaMPARI has the characteristics of permanent, large-scale labeling of immediate early genes, which enables a temporally precise "activity snapshot" of a large tissue volume. Professor Schreiter (Fosque et al, 2015) showed that when intracellular calcium is elevated, CaMPARI undergoes green-to-red conversion efficiently and irreversibly in response to a violet light shower in zebrafish, flies, head-fixed mice, and adult flies. Thus, the development of CaMPARI made it possible to efficiently study behavioral neuronal circuits in the entire brain.…”
mentioning
confidence: 99%
“…Therefore, the introduction of a new, permanent calcium molecular reporter that is able to record neural activity across the whole brain would be transformative, enabling focus on only marker neurons active during behavioral processes. Fortuitously, in 2015, Professor Schreiter's group (Fosque et al, 2015) designed a fluorescent sensor, the calcium-modulated photoactivatable ratiometric integrator (CaMPARI). CaMPARI has the characteristics of permanent, large-scale labeling of immediate early genes, which enables a temporally precise "activity snapshot" of a large tissue volume.…”
mentioning
confidence: 99%